PENDIDIKAN SEKS DALAM PANDANGAN ISLAM - Mira Rahmayanti Sormin (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Sex education in Islam is nothing new. Because when speaking aqidah, worship and morals then there includes sex education as in the discussion Toharoh and Sholat. The purpose of sex education in Islam is to safeguard the salvation and honor and purity of the generation of Islam in the midst of society. Thus both boys and girls will be maintained morally and religion until entering the family level clean and safe.Keywords: Education, Sex, Islamic View